Russia and Iran, 1780-1828 - Atkin, Muriel (Book collections on Project MUSE., 1980)
Modern Russo-Iranian relations date from the late eighteenth century, when after several centuries of commercial and diplomatic contact, the two nations entered a period of extended warfare for possession of the Caucasian borderlands, disputed territory t.